Влияние геронтологических изменений химических источников электрической энергии на основные энергетические показатели малоразмерных автономных подводных аппаратов - Щепцов, А. В. (НТУ "ХПИ", 2012)
The short analysis of chemical electric energy sources of dimension autonomous submarine vehicles is conducted in the article. Short descriptions of silver-zink sources of feed are resulted, their gerontology changes in the process of the protracted storage are shown, so influence of these factors on the basic power indexes of power-plants.
Keywords: аккумуляторные батареи; удельная мощность; серебряно-цинковая батарея; торпеда; электролит